On immigration and refugees - Dummett, Michael A. E. (London ; New York : Routledge, 2001)
Exploring the confused, and often highly unjust, thinking about immigration, Sir Michael Dummett questions the principles and justifications governing state policies, pointing out that they often conflict with the Geneva Convention
-- Contents t t t t t
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Government policy; Refugees -- Government policy; Refugees -- Government policy -- Great Britain; Racism -- Great Britain; Great Britain -- Emigration and immigration -- Government policy